A cross-cultural case study of consumers' communications about a new technological product - Moro, Sérgio (2020)
Using a case-study based approach, this research contributes to the standardisation versus adaptation debate in global marketing. It analyses the influence of the local culture dimension reflected in consumers’ comments in the Facebook platform regarding a new global technological product. Galaxy S8/S8+, launched worldwide in 2017. Consumers’ comments about this new smartphone were gathered and analysed for three cultural distinct English-speaking countries: Australia, India, and South Africa. The analysis’ procedure consisted of a text mining and topic modelling approach, including sentiment classification analysis, to discern and understand consumers’ responses to global brand communications. The findings indicate that cultural aspects still play a key role in consumers’ reactions to the product in each country, justifying the continued need for marketing strategies that conflate pursuing economies of scale with accounting for the cultural sensitivities of demand at country level. Evidence of consumers attitudes’ and behaviours’ homogenisation across countries is still limited.